Cathode flares during pulse breakdown of vacuum gaps; Proceedings of the IVth International Conference on Phenomena in Ionized Gases, Waterloo, Ontario, september 1-4, 1970 - Bazhenov G. P.; Baksht R. B.; Mesyats G. A. Gennady Andreyevich; Proskurovsky D. I.; Rotstein V. P.; Vavilov S. P. (1970, 1970)
В фонде НТБ ТПУ отсутствует